2008
DOI: 10.1007/s00420-008-0374-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood natural killer activity is reduced in men with occupational stress and job insecurity working in a university

Abstract: Not only anxiety and depression but also high levels of job strain and/or insecurity may affect the health status by reducing blood NK activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 22 publications
(27 reference statements)
6
28
0
Order By: Relevance
“…This result contradict with Probst and Lawler's study (2006) that found job security was a significant predictor (all p<.01) of employee job attitudes (β=.34), negative affective reactions (β= -.32), and job stress (β= -.29). The study of Boscolo et al (2008) showed that employees (over 40 years old) in a library showed higher values of job strain, anxiety and subjective symptoms and lower blood natural killer activity than the controls. The young employees with temporary employment showed high job insecurity and reduced blood NK activity, while the young sanitary staff with temporary position showed normal immune response.…”
Section: Discussionmentioning
confidence: 99%
“…This result contradict with Probst and Lawler's study (2006) that found job security was a significant predictor (all p<.01) of employee job attitudes (β=.34), negative affective reactions (β= -.32), and job stress (β= -.29). The study of Boscolo et al (2008) showed that employees (over 40 years old) in a library showed higher values of job strain, anxiety and subjective symptoms and lower blood natural killer activity than the controls. The young employees with temporary employment showed high job insecurity and reduced blood NK activity, while the young sanitary staff with temporary position showed normal immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Probst and Lawler (2006) found job security was a significant predictor (all p < .01) of employee job attitudes (β=.34), negative affective reactions (β= -.32), and job stress (β= -.29). The study of Boscolo et al (2008) showed that employees (over 40 years old) in a library showed higher values of job strain, anxiety and subjective symptoms and lower blood natural killer activity than the controls. The young employees with temporary employment showed high job insecurity and reduced blood NK activity, while the young sanitary staff with temporary position showed normal immune response.…”
Section: International Journal Of Research Studies In Psychology 13mentioning
confidence: 99%
“…In education organization, especially at higher education setting, many studies concluded that lecturer, staff or administration personnel reported from middle level to a higher level of job stress (Donders et al, 2003;Boscolo et al, 2008;Leung, Siu, & Spector, 2000;De Nobile & McCormick, 2007;Blix & Lee, 1991;Assadi, 2003;Jing, 2008). Ahsan et al (2009) stated many university academic staff in Malaysia now face more stress than past few years, because the increasing of pressure and competitiveness among universities in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Poor health behavior such as sleep deprivation and sleep loss is directly connected to a reduction of NK cells and increased inflammatory responses (24)(25)(26)(27) as well as depressed mood, stress symptoms, and obesity (10,28,29). Meanwhile, job stress has been shown to exert a negative impact on immune outcomes (30)(31)(32)(33)(34), and nocturnal sleep is known to be disturbed by overtime and job stress (23,(35)(36)(37). Based on this model, our study was undertaken to examine the association between overtime and cell-mediated immune markers, taking the potential mediating factors into account by stepwise analyses.…”
mentioning
confidence: 99%